Georgia : Eighth Review Under the Extended Fund Facility Arrangement-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Georgia has emerged from its second lockdown that was imposed in November 2020 following a sharp increase in COVID-19 cases. Vaccinations commenced in March 2021 and the country is now entering a critical stage in overcoming the pandemic. The lockdowns drove a contraction of around 6.2 percent of GDP in 2020, and a recovery is expected to take hold in the second quarter of 2021.